MEASURING TECHNOLOGICAL CAPABILITY AND BUSINESS PERFORMANCE POST-COVID ERA: EVIDENCE FROM SMALL AND MEDIUM-SIZED ENTERPRISES(SMEs) IN NIGERIA - Timilehin Olasoji OLUBIYI (Management & Marketing)
The coronavirus pandemic has resulted in a significant shock to businesses, with negative implications on present production capacity. Simultaneously, technology is being increasingly recommended as a significant means of minimising economic losses caused by the pandemic. Survival and lack of performance of small and medium-sized businesses continue to generate public discourse, intellectual interest, and attention. Though relationship between technological capabilities and business performance is more intricate than is often assumed. Inadequate technological capability is one of the primary factors contributing to business situation. Therefore, relationship between technological capability (TC) and business performance was examined amongst selected small and medium-sized businesses in Lagos State. This study used a survey research methodology with a sample size of 742 owner-managers of chosen SMEs in Lagos State. A questionnaire that was adopted and validated for the study was used to collect data. The questionnaire questions' Cronbach's alpha coefficients range from 0.77 to 0.88. The response rate to the survey was 94.5 percent. Using descriptive and inferential statistics, the acquired data was analysed (Pearson product moment correlation and regression analysis). The examination of the data demonstrated a significant association between technological capacity and small company performance (= 0.090, t = 3.029, F= 245.45 p.05). The conclusion of this research is that technical aptitude is a resource that enhances the performance of small businesses, with theoretical and practical consequences for businesses. It is recommended that the managers of small and medium-sized enterprises (SMEs) in Lagos State use their technology capability as a business resource, since this could help them generate new ideas or enhance existing goods.